POTENSI PENGEMBANGAN WISATA DI KOTA MATARAM BERDASARKAN PERSEPSI DAN PREFERENSI WISATAWAN - Lalu Adi Permadi; Emilia Septiani; Sri Darwini (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2021)
The purpose of this study was to determine the potential for tourism development in the city of Mataram based on tourist perceptions and preferences. The method of proving the research objectives uses descriptive research methods. Primary data collection will be carried out by in-depth interviews. The results of the study will show the tourism potential in the city of Mataram and how the development is based on the perceptions and preferences of tourists in tourist locations in the capital of NTB Province. The results of this study indicate that the perception of tourists about the potential for tourism development in the city of Mataram is high, meaning that tourists consider the city of Mataram still has the potential to be developed into a classy tourist destination. In general, based on tourist preferences for tourism development in the city of Mataram, the existing attractions, amenities, ancillaries and accessibility are still very possible to be developed. In general, the improvisations that expected by tourists are including facilities, the tourism attraction management and environmental cleanliness.